ANALISIS RASIO LIKUIDITAS, SOLVABILITAS DAN AKTIVITAS UNTUK MENILAI KINERJA KEUANGAN PADA KOPERASI UNIT DESA KARYA MUKTI DI KARYA HARAPAN MUKTI PERIODE TAHUN 2017-2019 - Munassolikah, Munassolikah (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2020)
The objectives to be achieved in this study are to find out and analyze based on the level of liquidity ratios, solvency and activity on the financial performance of the Karya Mukti village unit cooperative in Karya Harapan Mukti. The data used in this study is primary data, which is a source of data collected by researchers directly from the original source (not through intermediary media). This type of research uses quantitative methods, namely with the aim of analyzing and describing and collecting data in the form of numbers to describe data in financial reports to assess financial performance with liquidity, solvency and activity ratios. Based on the discussion conducted, it can be concluded that the Analysis of Liquidity, Solvency, and Activity Ratios carried out by the Karya Mukti Di Karya Harapan Mukti Village Unit Cooperative, has been good as can be seen from the financial reports at the end of the period which have been recorded in the financial books of the Karya Mukti Di Karya Cooperative Unit Mukti's Hope.